The Optimum Site Selection of Recycling Centers and Landfills for Demolition and Construction (D&C) Waste Using Geographic Information System (GIS) and Multi-Criteria Decision Analysis Case Study: Homs Governorate - محمد, عبير; شيبان, سامية; حسن, الاء (Latakia University Journal -Engineering Sciences Series, 2022)
Construction and demolition (C&D) waste is one of the main components of solid waste due to its large volumes and quantities. In the last ten years, due to the war on Syria, huge quantities of construction and demolition waste were generated, and this waste is often disposed of in municipal waste dumpsites or in illegal landfills without pre-treatment. Recycling center and landfill sites selection criteria are a complex process that depends on several conditions and regulations. In this study, Seven criteria were adopted, based on expert opinions (urban centers, tourist and archaeological centers, slope, NDVI, Water network, roads network, affected areas). Geographic Information Systems (GIS) and Multi-Criteria Decision Analysis (MCDA) technology are combined, together using the Hierarchical Analysis Process (AHP) and spatial analysis process to assess the spatial suitability for selecting sites for fixed recycling centers and landfills that don't exceed the administrative boundaries of Homs city and mobile recycling centers that don't exceed of the boundaries of the organizational scheme of the neighborhoods of Homs city. The criteria were represented in maps for both fixed and mobile centers in the GIS environment, and processed, reclassified and weighted according to the importance of each criterion, to get the result in two final maps showing the most suitable locations for the fixed and mobile recycling center. the 5 value representing the most suitable territories for selecting locations, while the results of the hierarchical analysis showed that the economic factors took the greatest importance.